The neural differences of arithmetic verification performance depend on math skill: Evidence from event‐related potential - Shiva Taghizadeh; Touraj Hashemi; Ali Jahan; Mohammad Ali Nazari (Wiley, 2021)
Abstract Aim Math skill is a basic need for an individual, as a career prospect. However, little is known about early brain processes of arithmetic between individuals with different math skill. Therefore, we questioned the modulation of the amplitude of an early negative component by math skill level in an arithmetic verification paradigm using event‐related potential (ERP). Methods Thirty‐six right‐handed participants were assigned in two groups of high‐ and low‐performing students. Their electroencephalogram was recorded while they completed an arithmetic verification task. Simple arithmetic operands were made by random digits from 1 to 9. Addition and subtraction operations were equally used in correct and incorrect responses. The accuracy scores, reaction times, and peak amplitude of the negativity in 200‐400 ms time window were analyzed. Results The high‐performing group showed significantly higher response speeds, and they were more accurate than the low‐performing group. The group × region interaction effect was significant. The high‐performing group showed a significantly greater negativity, particularly in parietal region, while the low‐performing group showed a significantly deeper negativity in frontal and prefrontal region. In the low‐performing group, there were significant peak amplitude differences between the anterior and posterior areas. However, such differences were not detected in the high‐performing group. Conclusion Students with different mathematical performance showed distinct patterns in early processing of arithmetic verification, as reflected by differences in negativity at 200‐400 ms at anterior and posterior. This suggests that ERPs could be used to differentiate math mastery at neural level which is beneficial in educational and clinical contexts.